Social Protection and Agricultural Production in ECOWAS: The Youth Unemployment Question - Osabohien, Romanus; Osuma, Godswill; Ndigwe, Chisom; Ozordi, Emmanuel (Journal of Social Economics Research, 2018)
In an economy youths play a very pivotal role as they constitute the greatest share of human resource which is essential in the economic development of a country. However, this potential in built in youth if not efficiently harnessed through gainful employment, portends a danger to the society. Youth unemployment can be likened to time dynamite if effective policies are not put in place to create employment for the youth especially in ECOWAS where graduate unemployment has been on the increase. On the other hand, the agricultural sector remains the most veritable tool for generating youth employment, poverty reduction and the attainment of food security. At any rate, the capacity of the agricultural sector to generate employment depends greatly on how the sector is been protected, which creates incentive to operate as business just as recently enshrined in agricultural transformation agenda; however, agricultural output can be enhanced by social protection programmes. Thus, this study examines the extent of social protection policies that are related to agricultural sector and how it influences the level of youth employment in ECOWAS using panel cointegration econometric analysis finds that in the long run, agriculture has the potential for ameliorating youth unemployment in ECOWAS.